Challenging Tasks, Motivated Cadets: Structural Validation of Task Challenge in ESP Reading for Aviation - Dani Chandra Yudho Pranoto; Rufi'i; Sabariah; Adi Bandono; Fajar Susanto (Langit Biru: Jurnal Ilmiah Aviasi, 2026)
English for Specific Purposes (ESP) plays a crucial role in preparing aviation cadets to comprehend technical documents and operate safely in global contexts. This study explores how perceived task characteristics—task relevance, benefit, and challenge—affect cadets' motivation in ESP reading tasks. Utilizing a quantitative-confirmatory design, data were collected from 95 cadets and analyzed through Structural Equation Modeling (SEM). The findings indicate that among the three constructs, only task challenge significantly predicted cadet motivation and confidence in reading. Task relevance and benefit, while positively perceived, did not produce statistically significant effects. The results highlight the central role of task difficulty in fostering engagement and persistence among cadets. The validated model underscores the importance of designing reading tasks that are optimally challenging to enhance motivation in high-stakes educational environments. This study provides empirical grounding for curriculum innovation in aviation English and contributes to the theoretical understanding of motivational dynamics in ESP contexts.